2009
DOI: 10.1259/bjr/99732265
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy using dynamic lymphoscintigraphy combined with ultrasound-guided fine needle aspiration in penile carcinoma

Abstract: The purpose of this study was to assess the utility of sentinel lymph node lymphoscintigraphy (SLNL) and ultrasound-guided fine needle aspiration cytology (FNAC) in patients with penile carcinoma. A prospective study was undertaken of 64 patients with stage T1 (or greater) clinically N0 squamous cell carcinoma of the penis. Patients underwent SLNL and bilateral groin ultrasonography with or without FNAC. Following intradermal blue dye, patients underwent unilateral or bilateral sentinel lymph node excision bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Bilateral LNM [21] . However, bilateral nodal involvement was presented in about 15% to 54% of all node-positive penile cancer patients in large case series 14 [ , 15,[22][23][24] .…”
Section: Number Of Metastatic Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral LNM [21] . However, bilateral nodal involvement was presented in about 15% to 54% of all node-positive penile cancer patients in large case series 14 [ , 15,[22][23][24] .…”
Section: Number Of Metastatic Lymph Nodesmentioning
confidence: 99%
“…Nowadays, more and more penile cancer patients with clinical negative lymph nodes were subjected to less invasive staging procedures such as sentinel nodal biopsy, and superficial or modified dissection . [21,[45][46][47][48][49] . Regardless the metastases deposit, extensive dissection is performed if one positive lymph node is found.…”
Section: N0mentioning
confidence: 99%
“…The sentinel lymph node(s) is thus located visually and with a probe. This has been accomplished via an open technique through skin flaps (54) or by first marking the overlying skin after detection of radioactivity (55)(56)(57). A criticism of DSNB is that the false negative rate is a relatively high 15-16% (56,58) with a consequently low sensitivity that has deemed the technique insufficient by some researchers (54).…”
Section: Assessment Of the Inguinal Nodesmentioning
confidence: 99%
“…These two modalities were used in a complementary fashion in a more recent paper. Sonographic criteria included increased size, abnormal shape, absence of echogenicity in the hilum, hypoechogenicity of the node, necrosis, and abnormal vascularity (57). At a median follow up of 11 months the respective sensitivity and specificity for US compared to DSNB were 74 and 77%; interestingly, US identified two patients with metastasis who were originally considered negative by DSNB (57).…”
Section: Assessment Of the Inguinal Nodesmentioning
confidence: 99%
“…Another prospective study of 64 patients with clinically N0 squamous cell carcinoma of the penis concluded that the combination of sentinel node biopsy and groin ultrasonography, with or without FNAC, is optimal in identifying occult nodal metastases. Ultrasonography alone is not adequate as a staging technique, and sentinel node biopsy alone might miss between 5% and 10% of metastases [26]. In patients with clinically palpable nodes, DSNB has been shown to be less useful due to false negative results as the lymphatics are blocked by the cancer cells [16].…”
Section: Dynamic Sentinel Node Biopsy (Dsnb)mentioning
confidence: 99%